2013
DOI: 10.1128/aem.02546-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Bacillus thuringiensis Cry1AMod Toxins under Regulation of cry3Aa Promoter and Single Cysteine Mutations in the Protoxin Region

Abstract: Bacillus thuringiensis Cry1AbMod toxins are engineered versions of Cry1Ab that lack the amino-terminal end, including domain I helix ␣-1 and part of helix ␣-2. This deletion improves oligomerization of these toxins in solution in the absence of cadherin receptor and counters resistance to Cry1A toxins in different lepidopteran insects, suggesting that oligomerization plays a major role in their toxicity. However, Cry1AbMod toxins are toxic to Escherichia coli cells, since the cry1A promoter that drives its exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…cry3Aa promoter is one of the cry promoters. A previous study demonstrated that Cry1AMod toxins from B. thuringiensis were efficiently produced under the regulation of the cry3Aa promoter . It was reported that an extracellular enzyme cellulase was highly upregulated during the stationary phase when under control of the cry3Aa promoter .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…cry3Aa promoter is one of the cry promoters. A previous study demonstrated that Cry1AMod toxins from B. thuringiensis were efficiently produced under the regulation of the cry3Aa promoter . It was reported that an extracellular enzyme cellulase was highly upregulated during the stationary phase when under control of the cry3Aa promoter .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that Cry1AMod toxins from B. thuringiensis were efficiently produced under the regulation of the cry3Aa promoter. 52 It was reported that an extracellular enzyme cellulase was highly upregulated during the stationary phase when under control of the cry3Aa promoter. 46 The srfA promoter has been used to enable comK and pnpA gene expression in B. subtilis, 60,61 which is an operon needed for the development of genetic competence in B. subtilis.…”
Section: Self-inducible Expression Of Tres In Recombinant B Subtilismentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the cry1Ac promoter can direct the expression of a variety of cry -like genes [ 4 ], such as cry1Ac , cry1Ab , cry1Ac5 , cry1Ac - av3 , cry2Ab27 , and cry8 . Similarly, the expression of Cry1AbMod/Cry1AcMod [ 5 ], Cry1Ac [ 6 ], Cry1c [ 7 ], Cry3A [ 8 ], Cry8Ga [ 9 ], and Cry69Aa1 [ 10 ] can be directed by the cry3A promoter. Recent reports have shown that some non- cry gene promoters with high-level activity were utilized for the expression of cry genes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%